Diagnostic RET genetic testing in 1, 058 index patients: A UK centre perspective. (13th January 2021) - Fussey, Jonathan Mark; Smith, Joel Anthony; Cleaver, Ruth; Bowles, Christopher; Ellard, Sian; Vaidya, Bijay; Owens, Martina
Abstract: Objective: Diagnostic germline RET analysis is offered to all patients with a diagnosis of medullary thyroid carcinoma (MTC), or other conditions associated with multiple endocrine neoplasia type 2 (MEN2) in the United Kingdom. Here, we report the experience of a single centre's germline RET analysis over a 21‐year period. Design: Retrospective case‐note review. Patients: All index patients referred to the Exeter Genomics Laboratory for diagnostic germline RET analysis between 1997 and 2018, and unaffected family members, undergoing predictive testing. Measurements: The rate and nature of pathogenic variant detection were recorded, as well as the indication for testing. Results: 1, 058 index patients and 551 unaffected family members were tested. The overall rate of pathogenic variant detection was 10.2% amongst index patients and 29% amongst unaffected family members. The commonest indication was isolated MTC, and amongst the 690 patients with isolated MTC, 68 (9.9%) were found to harbour a RET pathogenic variant. Of those with presumed sporadic MTC, 8.5% were found to harbour germline RET pathogenic variants, compared with 36.4% of those with a family history of MEN2‐associated conditions. Pathogenic variants were identified in 3.6% and 0% of patients with isolated phaeochromocytoma and primary hyperparathyroidism, respectively. Conclusions: Although the detection rate of RET germline pathogenic variants in patients with presumed sporadic MTC was significant, the overall detection rate in those with MTC was lower than expected in this series. Advances in RET analysis in response to reports of new variants over the last two decades are likely to have improved the pick‐up rate in recent years.